An SFL Approach to Promotional Practices in the Sentence Examples of Mission and Vision Statements - Iman Aib, Wasima Shehzad (JSSH, 2023)
This study concerns the use of promotional rhetoric reflected in mission and vision statements of international corporate firms. It mainly used transitivity system in systemic functional linguistics (SFL) to analyse the use of experiential processes in enacting promotional rhetorical moves. Based on hundred international companies’ mission and vision statements, we analysed the most recurrent experiential processes associated with each rhetorical move. Because companies aim to establish their social role in the corporate discourse community, they largely focus on promotional agendas. This requires them to write mission statements that define their nature, beliefs, and values. In conclusion, we found that mental and relational process are favoured linguistic practices used by corporate firms to write mission statements that focus on building public image. Iman Aib is a PhD scholar of English Linguistics in the Department of English at Air University Islamabad, Pakistan. Her research interests include ecolinguistics, genre analysis and critical discourse studies, and has published articles in Social Media + Society. Prof. Dr. Wasima Shehzad is serving as a professor in the Faculty of Social Sciences, Air University, Islamabad, Pakistan. She completed her PhD from University of Michigan under the supervision of John Swales. Her research interests are genre analysx1is, corpus linguistics and language policy, and has published numerous articles in journals such as Journal of Technical Writing and Communication. She is the author of the book Corpus Linguistics beyond the Word